The Implementation of the Sexual Assault Forensic Examination Telehealth Center: A Program Evaluation. Issue 3 (July 2021) - Miyamoto, Sheridan; Thiede, Elizabeth; Wright, Elizabeth N.; Berish, Diane; Perkins, Daniel F.; Bittner, Cynthia; Dorn, Lorah; Scanlon, Dennis
ABSTRACT: Introduction: Substantial disparities in the quality of post-sexual-assault (SA) care exist in the United States, particularly in rural areas. This study evaluates the implementation of the Sexual Assault Forensic Examination Telehealth Center, a program to improve SA care by increasing access to experienced sexual assault nurse examiners via telehealth, in three rural hospitals. Materials and Methods: The Dynamic Sustainability Framework (DSF) guided the implementation of the intervention. Survey and implementation data were evaluated 1 year after implementation using a nonexperimental pre–post design. Outcomes include patient and nurse perceptions of telehealth, local site nurse (LSN) confidence, and hospital protocol/policy changes. Results: Forty-one telehealth consultations were completed in the program's first year. An average of 34 system-level protocol changes were made per site. LSNs demonstrated statistically significant increases in confidence to provide SA care at 1 year. LSNs and telehealth sexual assault nurse examiners (expert consultants) reported that quality of SA care improved (87% and 83%, respectively). Patients highly rated the care they received (83%), reported telehealth improved care (78%), and reported feeling better after the examination (74%). Discussion: Using the DSF for implementation supported a tailored approach and successful adoption and also allowed for program iteration based on lessons learned. Conclusions: The Sexual Assault Forensic Examination Telehealth model resulted in improved local nurse confidence in provision of SA care, nurse perception of improvement in care quality, and high patient care experience ratings. These findings and the use of the DSF have implications for SA specialty care implementation in rural communities. Abstract : Supplemental digital content is available in the text.